2017
DOI: 10.1177/0961203317725588
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene FokI polymorphism in Egyptian children and adolescents with SLE: A case-control study

Abstract: Background Childhood-onset systemic lupus erythematosus (cSLE) is a lifelong autoimmune disorder. The vitamin D receptor (VDR) gene is a potential candidate gene for cSLE susceptibility. In this study, we aimed to investigate the FokI polymorphism in the VDR gene in Egyptian children and adolescents with SLE, to determine whether this polymorphism could be a genetic marker for cSLE susceptibility or disease activity and we also measured the serum level of 25-hydroxyvitamin D [25(OH) D] to assess its relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Ultimately, 19 studies were included in our meta‐analysis (Figure ). Sixteen studies compared circulating 25(OH)D levels between SLE patients and healthy controls (Table ); seven Studies provided the information about the deficiency, insufficiency, sufficiency of vitamin D in both SLE patients and healthy controls (Table ); 6 studies explored the correlations between disease activity of SLE and 25(OH)D levels (Table ). The NOS scores of included studies ranged from 6 to 8 stars, indicating each of the studies had high methodological quality (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ultimately, 19 studies were included in our meta‐analysis (Figure ). Sixteen studies compared circulating 25(OH)D levels between SLE patients and healthy controls (Table ); seven Studies provided the information about the deficiency, insufficiency, sufficiency of vitamin D in both SLE patients and healthy controls (Table ); 6 studies explored the correlations between disease activity of SLE and 25(OH)D levels (Table ). The NOS scores of included studies ranged from 6 to 8 stars, indicating each of the studies had high methodological quality (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen articles with 17 individual studies reported the circulating 25(OH)D levels of 1434 SLE patients and 1533 healthy controls. Compared with healthy controls, SLE patients had significantly lower 25(OH)D levels (pooled SMD = −1.63, 95% CI: −2.51 to −0.76), and significant heterogeneity was identified among these studies ( I 2 = 98.9%, P < .001) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations